Is GeneXpert MTB/RIF assay reliable for the diagnosis of pleural tuberculosis? - Muhammad Mudassir Shafiq; Muhammad Nadeem; Gul Afshan Zaidi; Naveed Arshad; Muzammil Khan; Zainab Niazi (Journal of Rawalpindi Medical College, 2022)
Introduction: Tuberculosis is the most common cause of infectious diseases related mortality globally. Tuberculous pleural effusion is a common presentation of extra pulmonary tuberculosis and a diagnostic challenge most of the time. The rapid diagnosis of tuberculous pleural effusion is essential for early treatment. GeneXpert is a new tool for rapid diagnosis but the ability to correctly diagnose of GeneXpert is a vital concern in the diagnosis of extra pulmonary tuberculosis.